Shakespeare on Screen: A Cinematic Exploration of Laurence Olivier's 1948 Film Adaptation of Hamlet - Baral, Binod Prasad (Literary Studies, 2024)
The paper explores the intricate process of translating Shakespeare's Hamlet from the pages to the screens, with a particular focus on the concept of transmediation. Hamlet, known for its linguistic and narrative complexities, presents a unique challenge in adapting its rich text to the visual medium. The study aims to unravel the layers of transmediality inherent in this transition. In doing so, the paper selects Laurence Olivier's 1948 adaptation of Hamlet as its case study. Employing translation theories, among others, by Regina Schober, Susan Basnett, and Linda Seger, the paper involves linguistic scrutiny of Hamlet's text, a comparative analysis of selected scenes between the play and the cinematic adaptation, and an interpretative analysis of fidelity and interpretation in Olivier's 1948 adaptation. The paper purposively selects three screenshots from the film and analyzes them. The analysis reveals the linguistic complexities embedded in Hamlet, shedding light on the challenges posed during the translation from page to screen. Additionally, the study evaluates the impact of transmediality and interpretation in cinematic adaptation, offering insights into how the original text's essence is preserved or transformed. The study explores the impact of directorial decisions on character portrayals, visual storytelling techniques, and the preservation of Shakespearean essence, offering insights into the lasting influence of Olivier's Hamlet on the field of cinematic interpretations.